2017
DOI: 10.1021/acs.jpcc.7b08919
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Water Molecules at the Silica–Ibuprofen Interface in Silica-Based Drug Delivery Systems Obtained through Incipient Wetness Impregnation

Abstract: The dynamical behavior of ibuprofen or benzoic acid (model molecule of ibuprofen) encapsulated in mesoporous silica is very specific as a very high mobility is evidenced at ambient temperature due to the existence of confinement effect. In this contribution, we demonstrate through variable temperature 1 H MAS NMR experiments that this specific dynamical behavior is also related to a fast chemical exchange that takes place between protons of the COOH group of the organic molecule and protons from water molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Since the pioneering work published by Vallett-Regi et al [ 1 ], a lot of papers on drug encapsulation in mesoporous silicas, mainly MCM-41, SBA-15, and their various modifications appear regularly, where SS NMR is used [ 136 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 ]. In many of them, ibuprofen is often employed as a model molecule for the study of host-guest interactions.…”
Section: Analytical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the pioneering work published by Vallett-Regi et al [ 1 ], a lot of papers on drug encapsulation in mesoporous silicas, mainly MCM-41, SBA-15, and their various modifications appear regularly, where SS NMR is used [ 136 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 ]. In many of them, ibuprofen is often employed as a model molecule for the study of host-guest interactions.…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…Moreover, the SS NMR study showed that the carboxylic proton of the ibuprofen was in a chemical exchange at room temperature with other protons, possibly from silica walls (SiOH) and/or water [ 180 ]. In the latter paper, the same group demonstrated examining ibuprofen and benzoic acid encapsulated in MCM-41 through incipient wetness impregnation method using variable temperature 1 H MAS NMR experiments [ 181 ]. The authors confirmed the presence of water molecules inside the pores of silica and their participation in the fast chemical exchange with protons of the COOH group of organic molecules at room temperature.…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…364 In a related study, they have applied variable temperature 1 H MAS NMR experiments to demonstrate the fast chemical exchange between protons of the COOH group of the organic molecule and protons from water molecules at the silica surface. 365 A different approach was adopted by Vega et al 366 to describe the adsorption/desorption dynamics of a drug model, namely a glycine-alanine dipeptide, onto SBA-15 at different degrees of hydration: the interaction with the hydrated surface was followed by deuterium MAS NMR, evaluating the size of the water clusters surrounding the adsorbed molecules. In this case, molecular dynamics (MD) simulations were used to support the measurements and model the adsorbate dynamics: a standard force field was used.…”
Section: Mesoporous Solids For Drug Deliverymentioning
confidence: 99%
“…Increased wettability of frameworks with lower SiO2:Al2O3 ratios(3), means that the sites available for hydrogen bonding may be occupied by water molecules. The importance of water molecules at the silica surface has been reported to be of significance in MCM-41 loaded with ibuprofen and the authors suggest that this is a consideration that is frequently overlooked when investigating drug delivery from silica (28). In addition, there is evidence that Brønsted Acid Sites can have mutual interaction via hydrogen bonding and, as a result, greater numbers of acid sites do not correlate with greater acidity (29).…”
Section: Effect Of Aluminium Contentmentioning
confidence: 99%